(untitled) (Scientific journal of the Fergana State University, 2024)
This article is the first to announce the bioecological characteristics of aphid species that cause serious damage to trees and shrubs growing in the Jizzakh, Syrdarya and Tashkent regions of the north-Eastern part of Uzbekistan.